USING GOOGLE HANGOUTS FOR TEACHING ENGLISH ONLINE - Afrianto Afrianto (Universitas Negeri Padang, 2016)
In the last five years or so, as part of its Google For Education program Google has released many applications which can be used by teachers to enhance their information technology (IT) based teaching and learning. Google hangout is one of popular applications which is now available for free, in addition to Gmail, Google Doc, Google Drive, and Google Talk. This paper introduces the use of this Google Hangouts as an alternative application for an online learning, including for delivering a virtual English classroom. Better internet networks around schools and campuses today have made this online learning more possible to happen. This paper will specifically discuss some theoretical and practical reasons why English teachers need to be more familiar with an online mode of learning. The distinctive features of the Google Hangouts which make it more promising for an online learning compared to other chat applications such as Skype and Yahoo Messengers will be addressed. Few samples of learning activities as well as possible challenges using the Google Hangouts will also be discussed. Although it requires more research on the effectiveness of this application to enhance students’ learning, it is believed that the use of this technology into a teaching process in many ways can fundamentally transform a traditional classroom.